(untitled) (Journal of Civil Engineering Researchers, 2023)
The growing population and urbanization have led to an increasing interest in constructing tall buildings, particularly in large cities. However, the frequent occurrence of earthquakes worldwide has necessitated the development of systems with high ductility and sufficient lateral stiffness. The special dual system of moment frame with bone connections and knee bracing systems are two examples of such systems. In this study, the seismic behavior of these two systems in combination with tall structures was investigated. Ten, thirteen, and sixteen-story frames with four different combinations of bone joints and knee bracing were analyzed using ETABS software. Linear and nonlinear static (pushover) analyses, as well as linear and nonlinear dynamic (time history) analyses, were conducted. Seismic parameters were then calculated for each case and compared. The results emphasized the importance of considering multiple factors and coefficients when evaluating the seismic performance of structures.